2017
DOI: 10.1073/pnas.1718471115
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the human PI4KIIIα lipid kinase complex

Abstract: Plasma membrane (PM) phosphoinositides play essential roles in cell physiology, serving as both markers of membrane identity and signaling molecules central to the cell's interaction with its environment. The first step in PM phosphoinositide synthesis is the conversion of phosphatidylinositol (PI) to PI4P, the precursor of PI(4,5)P and PI(3,4,5)P This conversion is catalyzed by the PI4KIIIα complex, comprising a lipid kinase, PI4KIIIα, and two regulatory subunits, TTC7 and FAM126. We here report the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 34 publications
3
96
0
Order By: Relevance
“…To this end, we selected PI4KIIIα (encoded by PI4KA , referred to hereafter as PI4KA). The enzyme exists as a large, 700-kD multi-subunit complex (Lees et al, 2017b; Dornan et al, 2018); however, the isolated carboxy-terminal fragment containing the helical and catalytic domain (PI4KA C1001 ) retains activity and can complement hepatitis C proliferation in PI4KA knockdown cells (Harak et al, 2014). Therefore, we fused this fragment to FKBP to facilitate chemically induced dimerization with FRB, targeted to distinct organelle membranes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we selected PI4KIIIα (encoded by PI4KA , referred to hereafter as PI4KA). The enzyme exists as a large, 700-kD multi-subunit complex (Lees et al, 2017b; Dornan et al, 2018); however, the isolated carboxy-terminal fragment containing the helical and catalytic domain (PI4KA C1001 ) retains activity and can complement hepatitis C proliferation in PI4KA knockdown cells (Harak et al, 2014). Therefore, we fused this fragment to FKBP to facilitate chemically induced dimerization with FRB, targeted to distinct organelle membranes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, these contributions do not explain the full capacity for PM synthesis, and the speed of the secretory pathway from the ER does not match the rate at which PM pools of PPIn can be turned over; instead, the activity of PI transfer proteins has been proposed to feed PPIn synthesis directly from the ER (Lapetina and Michell, 1973). More recently, specific PI transfer proteins such as Nir2 and TMEM24 have been identified in PM PPIn re-synthesis after activation of phospholipase C (Lees et al, 2017b; Dornan et al, 2018). Intriguingly, several of these studies found that simple over-expression of these transfer proteins can accelerate synthesis or elevate steady-state levels of PM PPIn (Chang et al, 2013; Kim et al, 2015; Lees et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…The localization of PI4KA to the PM is dependent on the presence of three interacting proteins: tetratricopeptide repeat protein 7 (TTC7), hyccin (FAM126A), and the palmitoylated scaffold EFR3 . The architecture of the macromolecular PI4KA complex was only recently described and revealed that the membrane‐associated PI4KA:TTC7:FAM126A assembly actually exists as a larger hexameric dimer of this core heterotrimeric unit, which relies on a combination of direct electrostatic interactions along with an extensive recognition of the unstructured C‐terminus of EFR3 for targeting to the PM (Figure ). It has also been suggested that an alternative complex, formed between PI4KA, EFR3, and the integral membrane protein TMEM150, may also target PI4KA to the PM and could function to enhance PI4KA catalytic activity .…”
Section: Production Of Polyphosphoinositide Species Within the Pmmentioning
confidence: 99%
“…The combined activities of PI4KA and Sac1 serve to establish a PtdIns4P gradient between the PM and ER that can be used to inform the directional movement of other lipids at ER‐PM contact sites. Notably, the catalytic domain of Sac1 (PDB Accession: 3LWT) is shown anchored within the ER using two transmembrane segments, while PI4KA is assembled as part of the recently described macromolecular complex (PDB Accession: 6BQ1), which also contains the interacting proteins tetratricopeptide repeat protein 7 (TTC7) and hyccin (FAM126A), and is tethered to the PM though an interaction with the unstructured C‐terminus of the palmitoylated scaffold EFR3 (PDB Accession: 4N5A) . For further details, please refer to Sections 3 and 6 of the text.…”
Section: Production Of Polyphosphoinositide Species Within the Pmmentioning
confidence: 99%